Toward a Typology of Missionary Medicine: A Comparison of Three Canadian Medical Missions in China before 1937 - Cheung, Yuet-Wah; New, Peter Kong-ming (Culture, 1983)
Until the Communist domination in 1949, medical missionaries had been the chief source of modern health care in China. While there is now a small but growing body of literature on medical missionaries and their work in China, studies in this area have treated missionary medicine as a homogeneous type of health care. This is a simplistic view of missionary medicine, as medical work organized by Christian missions has exhibited a variety of forms in Chinese society. The purpose of this paper is to offer a typology of missionary medicine, which will provide a useful framework for further research in this area. Medical missionary activities fell into three main dimensions, ranging from hospital and dispensary services, or “primary” medical work, to medical education and public health, or “secondary” medical work. While primary medical work was the sine qua non of every mission, the amount of medical resources allocated to secondary medical work varied tremendously among the missions. By using the concepts of “local” and “cosmopolitan,” two types of missionary medicine can be distinguished on the basis of the amount of secondary medical work carried out by a mission. Local medical missions devoted most resources to primary work, making few secondary efforts, whereas cosmopolitan medical missions allocated substantial resources to secondary work apart from maintaining primary work. The medical work of three Canadian missions in China from the turn of the twentieth century to 1937 will be used to illustrate the local-cosmopolitan typology. Also, the utility and implications of the typology for the study of health care in China will be discussed.